Shannon-Henderson, K.E. (2019). Religion and Memory in Tacitus’ Annals - McNamara, James (ARYS. Antigüedad: Religiones y Sociedades, 2020)
SHANNON - HENDERSON , KELLY E. (2019). Religion and Memory in Tacitus’ Annals. Oxford: Oxford University Press. 414 pp., 88,02€ [ISBN 978-0-1988-3276-8] [Book review]